Evaluation of Comparative Efficacy of Internal and External Use of Kushthadi Yoga in The Management of Ekakushtha (Psoriasis): Life Sciences-Ayurveda - U. Nimbhorkar, Ashish; Misar Wajpeyi, Sadhana (International Journal of Life Science and Pharma Research, 2023)
Ekakushthais one of the types of Kustha rogas. The Dosha predominance in Ekakushtha is Vata-kapaha. It exhibits clinical features of Aswedanam, Mahavastu, Ashaklopam and Kandu. On basis of clinical features Ekakushthais similar with Psoriasis by many scholars.External and internal factors, including as mild trauma, sunlight, infections, systemic medicines, and stress, can all provoke psoriasis. It can be treated by the use of topical, systemic antifungals, or corticosteroids as per modern science. Longterm use of these drugs may produce adverse effects or there may be more chances of recurrences after the stoppage of treatment. Hence there is need to study to study the Shodhana and Shaman chikitsa mentioned in Ayurveda whichare considered the most effective in twakvikar. The aim and objective of this study is to compare the effects of Kusthadi yoga and a placebo capsule in the treatment of Ekakushta (Psoriasis). A total of 40 patients were enrolled, and they were divided into 2 groups at random. For 30 days, Group A received Kushthadi Ointment and Kushthadi Capsule, whereas Group B received Kushthadi Ointment and Palcebo capsule. Patients were assessed for Kandu and PASI score on 0, 15thand 30th day. Both groups showed significant improvement in Kandu and PASI scale after treatment. But improvement was observed in a greater number of patients in group A treated with Kushthadi Ointmentand Kushthadi Capsule.The improvement was observed due to Kushthaghna, Kandughna, Krumighna, Tridoshshamaka, Raktavikarnashak,Rasayana andVirechakaproperties of ingredients of Kushthadi yoga.It possesses antipsoriatic, antiinflammatory, antipruritic, antibacterial and antioxidants which helps in reducing symptoms. Kushthadi Yoga is effective in the management of Ekakushtha and ifit is given internally along with local application then it shows better results. Keywords: , , ,